UPAYA MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA PADA MATERI JAM MELALUI PENGGUNAAN MEDIA PERMAINAN KINCIR PADA SISWA SD KELAS II - Neneng Suryani; Iis Nurasiah; Efi Kurniasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low ability of second-grade elementary school students to understand the concept of time remains a challenge in mathematics learning. Students often experience difficulties distinguishing the functions of the hour and minute hands and reading time accurately. This condition indicates the need for concrete and engaging learning media that are appropriate to students’ developmental characteristics. This study aimed to improve students’ understanding of time concepts through the use of the Pinwheel Clock media and to describe the learning process that supports student participation and engagement. This study employed Classroom Action Research (CAR) conducted from April to May 2026 with 17 second-grade elementary school students as participants. The research was carried out in two cycles consisting of planning, action, observation, and reflection stages. Data were collected through observation, learning achievement tests, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques by comparing students’ learning outcomes in each cycle. The results showed that the use of the Pinwheel Clock media improved students’ understanding of reading time. Student learning completion in the pre-cycle was 29% and Cycle I reached 41% or 7 out of 17 students, then increased to 88% or 15 out of 17 students in Cycle II. In addition, students demonstrated higher levels of participation, enthusiasm, and engagement throughout the learning process. The visual and interactive characteristics of the media helped students understand time concepts more concretely and meaningfully. In conclusion, the use of the Pinwheel Clock media was effective in improving students’ understanding of time concepts in mathematics learning for second-grade elementary school students.